Cross-cultural adaptation of the upper limb functional index in Arabic - Albahrani, Yousef A.; Alshami, Ali M. (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The upper limb functional index (ULFI) is a widely used self-reported outcome measure questionnaire with robust psychometric properties to assess the upper limb musculoskeletal disorders (UL-MSDs). This study aimed to adapt the ULFI cross-culturally in Arabic (ULFI-Ar) and to examine its face validity, content validity, internal consistency, criterion validity, and interpretability. Methods: In this observational cross-sectional study, the English version of ULFI was cross-culturally adapted to the Arabic language through double forward and backward translations, following the recommended guidelines. Interviews with participants and reviews by experts were used to assess the face and content validity of the prefinal version of ULFI-Ar. Internal consistency was determined by Cronbach’s alpha coefficient (a). Criterion validity was analyzed by correlating the ULFI-Ar with the Arabic version of the Disabilities of the Arm, Shoulder, and Hand (DASH-Arabic) using Pearson’s correlation coefficients. Results: A total of 54 participants reported no major language barriers or difficulties in completing the ULFI-Ar. The participants’ interview demonstrated adequate face validity. The review by experts showed that the content validity was excellent (content validity index = 0.81 – 1.00 for each item and 0.96 for the scale). The ULFI-Ar showed high internal consistency (a = 0.88). For criterion validity, there was strong correlation with the DASH-Arabic (r = -0.802, p < 0.0001) and moderate correlation with NPRS-Arabic (r = -0.502, p < 0.0001). Conclusions: The ULFI-Ar was easy to complete with no linguistic difficulties. The results demonstrate the suitability of using the ULFI-AR for Arabic-speaking patients with UL-MSD.